Catch-and-release behavior of anglers in Tasik Muda, Kedah - Shaefe, Muhammad Adi Syarqawi; Kamaruddin, Izharuddin Shah (Universiti Putra Malaysia Press, 2020)
This study aimed to identify the basic sociodemographic background, catch-and-release behavior, and preferred fish species of anglers in Tasik Muda, Kedah, Malaysia. During the study period, anglers who fished in Tasik Muda were requested to answer a survey questionnaire through a face-to-face on-site sampling technique. Based on the theory of planned behavior (TPB), the questionnaire measured four variables, namely, attitude, subjective norm, perceived behavioral control, and intention. Eight types of fish species were included as choices. The results show that most of the respondents were male (90.5%) with a mean age of 36.59 ± 8.80 years old. Furthermore, most of the respondents were married (77.1%), self-employed (45.8%), and obtained an education of up to Sijil Pelajaran Malaysia level (40.3%). Scores for perceived behavioral control were above average (3.94 ± 0.78), thereby indicating that this variable may have a bigger impact in performing catch-andrelease fishing. The anglers also demonstrated their subjective norm (3.58 ± 0.75), intention (3.56 ± 0.89), and attitude (3.39 ± 1.07) toward catch-and-release fishing. In terms of fish species, most of the anglers preferred Malaysian mahseer (Tor tambroides) (4.65 ± 0.66), snakehead (Channa striata) (4.54 ± 0.82), copper mahseer (Neolissochilus soroides) (4.51 ± 0.83), and hampala barb (Hampala macrolepidota) (4.47 ± 0.80). However, the TPB variables and fish preferences differed when analyzed against the basic sociodemographic background of the anglers. This study provides the basic data and information on anglers engaged in recreational fishing in Tasik Muda, Kedah.